Essential role of the N-terminal region of TFII-I in viability and behavior - Lucena, Jaume (2010)
Background: GTF2I codes for a general intrinsic transcription factor and calcium channel regulator TFII-I, with high and ubiquitous expression, and a strong candidate for involvement in the morphological and neuro-developmental anomalies of the Williams-Beuren syndrome (WBS). WBS is a genetic disorder due to a recurring deletion of about 1,55- 1,83 Mb containing 25-28 genes in chromosome band 7q11.23 including GTF2I. Completed homozygous loss of either the Gtf2i or Gtf2ird1 function in mice provided additional evidence for the involvement of both genes in the craniofacial and cognitive phenotype. Unfortunately nothing is now about the behavioral characterization of heterozygous mice. Methods: By gene targeting we have generated a mutant mice with a deletion of the first 140 amino-acids of TFII-I. mRNA and protein expression analysis were used to document the effect of the study deletion. We performed behavioral characterization of heterozygous mutant mice to document in vivo implications of TFII-I in the cognitive profile of WBS patients. Results: Homozygous and heterozygous mutant mice exhibit craniofacial alterations, most clearly represented in homozygous condition. Behavioral test demonstrate that heterozygous mutant mice exhibit some neurobehavioral alterations and hyperacusis or odynacusis that could be associated with specific features of WBS phenotype. Homozygous mutant mice present highly compromised embryonic viability and fertility. Regarding cellular model, we documented a retarded growth in heterozygous MEFs respect to homozygous or wild-type MEFs. Conclusion: Our data confirm that, although additive effects of haploinsufficiency at several genes may contribute to the full craniofacial or neurocognitive features of WBS, correct expression of GTF2I is one of the main players. In addition, these findings show that the deletion of the fist 140 amino-acids of TFII-I altered it correct function leading to a clear phenotype, at both levels, at the cellular model and at the in vivo model.